Serum markers associated with treatment response and survival in non-small cell lung cancer patients treated with anti-PD-1 therapy. (July 2020) - Takada, Kazuki; Takamori, Shinkichi; Yoneshima, Yasuto; Tanaka, Kentaro; Okamoto, Isamu; Shimokawa, Mototsugu; Oba, Taro; Osoegawa, Atsushi; Tagawa, Tetsuzo; Takenoyama, Mitsuhiro; Oda, Yoshinao; Nakanishi, Yoichi; et al.
Highlights: dNLR is a novel serum inflammatory marker. dNLR is calculated from white blood cell concentration and neutrophil count. dNLR was associated with treatment response in NSCLC treated with anti-PD-1 drugs. dNLR was an independent prognostic factor in NSCLC treated with anti-PD-1 drugs. dNLR might be the most important factor for the efficacy of anti-PD-1 therapy. Abstract: Background: Several serum markers have been associated with treatment response and clinical outcome in non-small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors. Materials and methods: We performed univariate and multivariate analyses on 226 patients with advanced or recurrent NSCLC treated with anti-programmed cell death-1 (PD-1) therapy. The cut-off values for body mass index (BMI), albumin (Alb), and serum inflammatory markers were determined by receiver operating characteristic curve analyses. Tumor response was assessed by computed tomography according to the Response Evaluation Criteria in Solid Tumors, version 1.1. Results: BMI ≥ 19.1 kg/m 2 and derived neutrophil-lymphocyte ratio (dNLR) < 2.79 were independent predictors of overall response, and Alb ≥ 3.5 g/dL and dNLR < 2.79 were independent predictors of disease control. Analyses of survival revealed that Alb < 3.5 g/dL, dNLR ≥ 2.79, lymphocyte-monocyte ratio < 2.12, and red blood cell distribution width ≥ 15.9 % were independent predictors of both progression-free and overall survival. Moreover, these markers tended to have a strong impact on survival, especially among patients with programmed cell death-ligand 1 tumor proportion score ≥ 50 %. Conclusions: dNLR might be the most important factor for predicting the efficacy in NSCLC patients treated with anti-PD-1 therapy.